Presynaptic muscarinic receptors inhibiting active acetylcholine release in the bullfrog sympathetic ganglion. - Koketsu, K. (Nature Publishing Group, 1982)
1 The effects of bethanechol and atropine on the release of acetylcholine (ACh) from bullfrog sympathetic preganglionic nerve terminals were examined electrophysiologically. 2 Bethanechol (1 mM) caused no depolarization of sympathetic preganglionic nerve terminals, whereas carbachol or ACh in the same concentration induced marked depolarizations of these terminals. 3 Bethanechol (10 microM) depressed the amplitude of fast excitatory postsynaptic potentials (e.p.s.ps) recorded in Ca2+-high Mg2+ solution, without depolarizing ganglion cells. The quantal content measured from these fast e.p.s.ps by the variance method showed a significant reduction. 4 Amplitudes of both miniature e.p.s.ps and ACh-potentials induced by iontophoresis of ACh were not affected by addition of bethanechol (10 microM). 5 The depressant effect of bethanechol (10 microM) on fast e.ps.ps disappeared in the presence of atropine (3 microM). 6 Atropine (3 microM) increased the quantal content measured from fast e.p.s.ps recorded in low Ca2+-high Mg2+ solution. 7 The depressant effect of bethanechol (10 microM) on fast e.p.s.ps was unaffected by alpha-adrenoceptor blocking agents (phenoxybenzamine (10 microM) or phentolamine (10 microM). 8 These results suggest that presynaptic nerve terminals in bullfrog sympathetic ganglia possess a muscarinic receptor which inhibits active release of ACh.